Efeito do ângulo de derrubada no rendimento do Feller Buncher em floresta de Eucalyptus spp - Millani, Thais Maria [UNESP] (2015)
The high need for forestry products results in constant demand for increase in wood growth, reflecting in the evolution of forestry mechanization. The forestry mechanized harvesting promotes greater efficiency on the process, providing products final costs most competitive to trade and people training. This study aimed to carry out an operational analysis of eucalyptus mechanized harvest with Feller Buncher felling trees at different angles. Were applied two treatments composed by different felling angles, the first being formed by wood bundles disposed at 0o, 45 o, 135 o and 180 o from the planting alignment and the second formed by wood bundles disposed at 0 °, 45 °, 90 °, 135 ° and 180 ° from the planting alignment. The operational analysis of Feller Buncher was carried out by the study of time and motion using continuous timing. Were timed 400 operational cycles for each treatment, composed by timed effective activities, aiming improve on operational performance. In the first treatment most of bunchers were disposed at felling angles of 45° and 135°, while in the second treatment most of bunchers were disposed in the felling angle of 90°. The felling angle affects the yield and cycle time. The angle of 45o presented the shorter cycle time and higher efficiency in this study. There was statistical difference between the times and the efficiency in treatments 1 and 2. The felling angles of 0°, 45o, 135o and 180o showed less time and higher efficiency in relation to the felling angles of 0°, 45°, 90°, 135o and 180o. Less variation of felling angles showed better efficiency and cycle time.